Omnichannel marketing and beacon technologies: experience and prospects in Europe - A. A. Sazonov; M. V. Sazonova (Управление, 2021)
The article presents the main results obtained from the use of Omnichannel marketing strategy and Beacon technologies in the field of European trade, determines by the difference between multichannel and omnichannel marketing strategies. For the development of the main directions of digital technologies in the field of marketing, proposed in the works of D.J. Peltier, it is necessary to update the components included in the structure of integrated marketing communications. The authors established that under the influence of modern digital marketing technologies, it is necessary to redefine the disparate points of contact with customers that affect the process of consumer engagement and profit generation due to the use of various Omnichannels. Developing practical aspects of the Omnichannel retail strategy put forward by Yu. Melantiu needs to take into account that at the intersection of effective Omnichannel marketing and strategic initiatives, marketers get the opportunity to attract new customers and increase the level of brand loyalty. The paper presents the structure of beacon technology, gives the results of its application in European trade. The study reveals that the emergence of Omnichannel marketing leads to the destruction of the structure fields in the already available points where brands and consumers come into contact. The purpose of the article is to assess the level of application of omnichannel marketing technologies and beacon technologies by European retailers in order to develop a recommendation base necessary for the further effective development of omnichannel marketing in European countries. The authors propose a scheme of interaction between beacon technologies and information technology integrators within the framework of the omnichannel marketing strategy. The study performs a comparative analysis of multichannel and omnichannel marketing strategies. The authors make conclusions related to the development of omnichannel marketing in European countries, as well as determine the possibility of integrating beacon technologies into the omnichannel marketing system.